Experiences of Family Separation for Adults Who Immigrate Alone: Lessons for Social Work Practice and Research - Martin, Beth (Canadian Social Work Review / Revue canadienne de service social, 2017)
This study explored lived experiences of migration and settlement for adults who migrated to Canada on their own and were separated from family and friends. A theoretical framework drawing on ecological theory and adult attachment theory was used to analyze data collected from exploratory, in-depth interviews with seven adults who arrived in Canada through a range of immigration streams. Themes previously identified in research on unaccompanied minors, refugees, and migrants with precarious status were found in this study to be experienced also by those who had arrived through other immigration streams. Participants described how they associated separation from various family members with negative experiences of emotional isolation, and both negative and positive experiences of social isolation. Participants discussed changes in relationships that occurred prior to migration and continued after arrival, particularly when separation was lengthy. Participants drew upon various personal and environmental resources to help mitigate negative impacts of social isolation, but were less effective in countering emotional isolation. The findings have implications for social workers working both with individual immigrants separated from family members and with immigrant families that have been reunited. In this paper, the author also suggests areas for further research and social work advocacy.